Peran Bmt Al-Hijrah Kota Sorong Dalam Meningkatkan Ekonomi Umkm di Masa Pandemi Covid-19 - Abdul Zamal Nur; Fatma Sari; Nur Faizah (At-Thariqah: Jurnal Ekonomi, 2022)
The Covid-19 pandemic has had a huge impact on the economy. One of the ways that Micro, Small and Medium Enterprises (MSMEs) do to improve their economy is by seeking capital loans for their businesses. The role of financial institutions is needed in this regard. Capital loans can be obtained by MSME actors through microfinance institutions which are now growing rapidly in Indonesia. one of them is through BMT which provides financing and assistance to MSME customers. The results in this study indicate that the financing for MSMEs in BMT Al-Hijrah includes mudharabah, musyarakah, murabahah, and ijarah financing. As for the role of BMT Al-Hijrah during the COVID-19 pandemic, namely, financing carried out by BMT Al-Hijrah, providing relief from delays in payment of financing customer deposits, and distributing business capital assistance from the West Papua Cooperatives and SMEs Service. Judging from the contribution of these roles, the benefits felt by BMT Al-Hijrah MSME customers are for additional capital, increasing the procurement of merchandise, and improving business premises, and the funds obtained are also for living necessities during the COVID-19 pandemic.